Math Comics, Vectors, and the Strategy of Preview, Question, Read, Reflect, Recite, Review (PQ4R) - Kristina Kurniati; Rully Charitas Indra Prahmana; Alberta Parinters Makur; Silfanus Jelatu (Formatif: Jurnal Ilmiah Pendidikan MIPA, 2018)
The study aims to develop a mathematical comic’s media of vector material on the subject of vector notation and its operation through the strategy of Preview, Question, Read, Reflect, Recite, Review (PQ4R). Furthermore, the product implemented for senior high school students at SMA N 1 Langke Rembong 2017/2018 academic years to know the quality of the media. The instruments used in this research are mathematical comic evaluation sheet, student response questionnaire, and student achievement mathematics test. The learning aid develops through the development model of ADDIE namely Analysis, Design, Development, Implementation, and Evaluation. The results show that the validity of learning aid with the criteria passes without revision based on the validator assessment of the material, language, and media with the score of 4.00, 4.00, and 3.75 respectively. For the aspect of practicality, the media includes in passing criteria and appropriate to be used without revision based on teacher's assessment of comic mathematics with score 4.47 and student response questionnaire with score 3.64 with criteria well used in the learning process. Lastly, the potential effects of mathematical comics include in the high standards based on student achievement test with the percentage of mastery by 75%.